2022
DOI: 10.2478/cee-2022-0049
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Design of Road Traffic Noise Reducing Devices

Abstract: The authors present the first ideas of contextual design (CD) of noise barriers (NB), which integrates acoustic, architectural, environmental, and economic aspects of a holistic approach to the design of these engineering structures. The paper presents an example of an economic subsystem of CD focused on the economical optimization of NBs with an emphasis on the circular economy. It also demonstrates the significant potential of NBs to improve the architectural visual appearance of built-up areas as essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Based on the evaluated mechanical characteristics of the MS road surface, it can be concluded that even in 2024, the implemented road meets the criterion for protection against the adverse effects of frost, even when considering climate changes [25,26]. Additionally, it exhibits low levels of particulate matter [27] and noise pollution [28], adhering to the principles of pavement contextual design [29].…”
Section: Discussionmentioning
confidence: 92%
“…Based on the evaluated mechanical characteristics of the MS road surface, it can be concluded that even in 2024, the implemented road meets the criterion for protection against the adverse effects of frost, even when considering climate changes [25,26]. Additionally, it exhibits low levels of particulate matter [27] and noise pollution [28], adhering to the principles of pavement contextual design [29].…”
Section: Discussionmentioning
confidence: 92%
“…From the above, we can clearly see the authors' perception of green infrastructure as an integral part of the quality of life. Currently, when designing integrated transport infrastructure, the priority focus is on its safety [5], [6], minimizing negative environmental impacts [7] to [9], preference for urban transport [10], and only marginal attention is paid to its influence on psychological health, in which green infrastructure can play a significant positive role.…”
Section: Civil and Environmental Engineeringmentioning
confidence: 99%
“…In the field of sustainability of material and environmental engineering of transportation structures, the authors address the possibilities of using industrial waste (waste from automotive production) in roadway structures and noise barriers [ 11 , 12 ]. In the course of the production of automobiles and their textile parts, as well as in the recycling of vehicles at the end of their service life, which involves separated textile parts, a variety of textile materials with different specific qualities are produced.…”
Section: Introductionmentioning
confidence: 99%